An Analysis of Speech Act Used in London Has Fallen Movie - Zulfa Tutuarima; Nuraeningsih Nuraeningsih; Rusiana Rusiana (Vision: Journal for Language and Foreign Language Learning, 2018)
The most significant thing in speech act is the message that speaker wants to convey. It means when using language is not only produces a sentence but also perform an action. The aims of the research are (i) to find out the kinds of speech act used in London Has Fallen Movie (ii) to find out the way of speech act and the classifications of illocutionary act used in London Has Fallen Movie. This research uses descriptive qualitative research. This research figures out the kinds of speech act and the classifications of illocutionary act used in London Has Fallen Movie. The result of the research shows that: (i) there are 76 utterances of speech act used in London Has Fallen Movie which is the most dominant is illocutinary act consist of 37 utterances. (ii) there are 99 utterances of the classifications of illocutionary act and the most dominant categories are directive with 32 utterances and expressive with 23 utterances.